2016
DOI: 10.5812/ircmj.12805
|View full text |Cite
|
Sign up to set email alerts
|

Management of Esophageal Burns Caused by Caustic Ingestion: A Case Report

Abstract: Introduction:Domestic and industrial swallowing of caustic substances can cause acute and chronic injuries. In the acute phase of care, focus is on the immediate control of tissue damage and perforation, and in the chronic phase, the focus is on the treatment of pharyngeal narrowing and impaired swallowing.Case Presentation:The patients of this report were an 18-year-old man and a 20-year-old woman, who had esophageal burns after ingesting chemicals, and for solving their nutritional problems, such as difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…Bita Shahbazzadegan et al reported two cases of caustic ingestion-related gastric and esophageal burns that underwent surgical replacement of the esophagus with the left colon and transverse colon with anastomoses of esophagus-transverse colon at neck and left colon-stomach in the abdomen. Nevertheless, stomachs in both cases were still in preserved conditions [7].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Bita Shahbazzadegan et al reported two cases of caustic ingestion-related gastric and esophageal burns that underwent surgical replacement of the esophagus with the left colon and transverse colon with anastomoses of esophagus-transverse colon at neck and left colon-stomach in the abdomen. Nevertheless, stomachs in both cases were still in preserved conditions [7].…”
Section: Discussionmentioning
confidence: 92%
“…To our best knowledge, these are the first two cases that both esophagus and stomach were resected concurrently due to the consumption of corrosive chemicals, which were then reformulated using ileum-right colon segment in the literature. The colon has been commonly claimed as a potential part to replace the esophagus and stomach in a wide range of previous medicinal reports [6,7,11,12]. In our surgery, we used an additional 8 cm of ileum connected with Bauhin valve to eliminate any refluxing symptoms, whereas both the cardia and the pyloris were removed to increase the quality of life for patients post-operatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bassiouny IE và cộng sự thông báo sử dụng đại tràng để thay thế cho thực quản bỏng do chất ăn mòn [7], Bita Shahbazzadegan và cộng sự báo cáo hai trường hợp bỏng thực quản và dạ dày do hóa chất ăn mòn đã được phẫu thuật thay thế thực quản bằng đại tràng trái và đại tràng ngang. Tuy nhiên, cả hai trường hợp này dạ dày vẫn được bảo tồn bằng miệng nối thực quản -đại tràng và đại tràng -dạ dày [8].…”
Section: Bàn Luậnunclassified
“…The literature is rife with case studies and reports of esophageal injuries that were caused by exposure to chemicals [7][8][9]. Esophageal ulcers are also known to be directly linked with aphthous stomatitis, malignancy and infections [10].…”
Section: Gastro Med Resmentioning
confidence: 99%